Efektivitas Media Pembelajaran Ubur-Ubur Terhadap Peningkatan Minat Belajar Siswa Pada Mata Pelajaran Bahasa Indonesia Di Mi Nurul Huda Banjarsari: Jellyfish Learning Media, Learning Interest, Indonesian Language Learning (Jurnal Sekolah Dasar, 2026)
The purpose of this study was to determine the effect of jellyfish learning media on increasing students' interest in learning Indonesian at MI Nurul Huda Banjarsari. This study used one paired class, so it used a quantitative method using t-test data analysis. Observations, questionnaires, interviews, documentation, reading books, journals, websites and other written documents became the sources of this research. The research subjects selected were the principal, Indonesian subject teachers, and 35 students. Based on the results of the study, it was concluded that jellyfish learning media had an impact on increasing students' enthusiasm in learning Indonesian at MI Nurul Huda Gunungsari. This was indicated by the results of the t-test and normality test which showed a Sig. (2-tailed) value of 0.000 <0.05. The result, namely Ho was rejected and Ha was accepted, which indicated that the use of jellyfish media had a positive effect on increasing students' interest in learning. Jellyfish learning media has been proven to be able to create an interesting, interactive, and meaningful learning atmosphere. This has a positive impact on increasing students' interest in learning. Therefore, it is highly recommended that appropriate and interesting media be used more widely in Indonesian language learning at the Madrasah Ibtidaiyah level to improve the quality of education.